2005
DOI: 10.1093/jxb/erj002
|View full text |Cite
|
Sign up to set email alerts
|

Construction costs, chemical composition and payback time of high- and low-irradiance leaves

Abstract: The effect of irradiance on leaf construction costs, chemical composition, and on the payback time of leaves was investigated. To enable more generalized conclusions, three different systems were studied: top and the most-shaded leaves of 10 adult tree species in a European mixed forest, top leaves of sub-dominant trees of two evergreen species growing in small gaps or below the canopy in an Amazonian rainforest, and plants of six herbaceous and four woody species grown hydroponically at low or high irradiance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
148
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(168 citation statements)
references
References 59 publications
15
148
0
5
Order By: Relevance
“…Poorter et al (2006aPoorter et al ( , 2006b) provided an independent, objective, and continuous measure of the regeneration light requirements of the species (i.e., the inverse of shade tolerance) by analyzing the crown exposure (CE) for each species in relation to the height of individual trees. This allows one to go beyond the subjective classiWcation into pioneers and shade tolerants, and to show how species traits change gradually and continuously with the light requirements of the species.…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations
“…Poorter et al (2006aPoorter et al ( , 2006b) provided an independent, objective, and continuous measure of the regeneration light requirements of the species (i.e., the inverse of shade tolerance) by analyzing the crown exposure (CE) for each species in relation to the height of individual trees. This allows one to go beyond the subjective classiWcation into pioneers and shade tolerants, and to show how species traits change gradually and continuously with the light requirements of the species.…”
Section: Study Sitementioning
confidence: 99%
“…The CE can be measured repeatedly (average diVerence between two independent observers is 0.1 § 0.01 SE), and there is a good relation between CE and both canopy openness and incident radiation (Davies et al 1998;Clark et al 1993;Keeling and Phillips 2007). For each species the CE was related to tree height, using a multinomial regression analysis (Poorter et al , 2006a(Poorter et al , 2006b). Using the regression equation, the average population-level CE at a standardized height of 2 m (juvenile CE) was calculated.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Two recent studies encourage our growing sense that sometimes the retention of leaves in deep shade may involve more than repayment of the mortgage. First, measurements and modelling in European forests by Poorter et al (2006) showed that in spite of 5-to 20-fold larger payback times than outer canopy leaves, investment in inner canopy leaves exposed to as little as 5% of seasonal irradiance paid a dividend. Second, Reich et al (2009) reported that, in the dry sclerophyll woodland of eastern Australia, leaves of most species retained positive carbon balance (remained productive) throughout their typical life-span.…”
Section: The Need To Strengthen Linkage Between 'Insights Of Economicmentioning
confidence: 99%